Change of Oral Mucus in Patients with Diabetes - Holboeva Nasiba Asrorovna; Burhanov Muhriddin; Lolashev Shohruh (Genius Journals, 2022)
This article talks about changes in the mucous membrane of the oral cavity in patients with diabetes. Diabetes mellitus is associated with a greater likelihood of developing certain oral mucosal disorders.
Keywords: Medicine; disease; patient; oral mucosa